A green and simple method for synthesizing three-dimensional carbon gel materials for electrochemical energy storage

By using water-soluble calcium salts and carbonates to prepare calcium carbonate nanoparticles and combined with organic carbon sources for pyrolysis, the complex and time-consuming problems of traditional technology are solved, and simple and efficient three-dimensional carbon gel preparation is achieved, suitable for commercial use Use.

CN118651854BActive Publication Date: 2024-12-13FUYANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411137569.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The traditional three-dimensional carbon aerogel preparation technology is complex, time-consuming, high cost and high risk, which limits its potential in industrial-scale applications.

Method used

Calcium carbonate nanoparticles are prepared by water-soluble calcium salts and carbonates, mixed with organic carbon sources and binders for aging, followed by pyrolysis and carbonization under the protection of inert gas, and finally used protonic acid etching to remove calcium carbonate nanoparticles , obtain a three-dimensional carbon gel.

Benefits of technology

It realizes the preparation of three-dimensional carbon gels with simple process, short time and low cost, reduces the use of organic solvents, promotes the resource utilization of waste, and obtains efficient, environmentally friendly and economical porous carbon gel materials, suitable for commercialization. application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118651854B_ABST
    Figure CN118651854B_ABST
Patent Text Reader

Abstract

The present application relates to the field of aerogel technology, and specifically discloses a method for green and simple synthesis of three-dimensional carbon gel materials that can be used for electrochemical energy storage. Compared with traditional preparation methods, the method of the present application is simpler in process, less time-consuming and less costly. During the entire preparation process, almost no organic solvents are required, thereby greatly reducing the emission of volatile organic compounds (VOCs). In addition, the selection range of organic carbon sources is wide, and can be wastes such as agricultural straw and domestic garbage, which not only promotes the resource recycling of waste, but also reflects the green and environmentally friendly characteristics of this method. The three-dimensional carbon gel preparation method of the present application, with its multiple advantages such as high efficiency, environmental protection, and economy, has opened up a new path for the sustainable development of carbon aerogel materials, fully overcomes the defects in related technologies, and is suitable for commercial use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aerogel technology, and more specifically, to a method for green and simple synthesis of three-dimensional carbon gel materials that can be used for electrochemical energy storage. Background Art

[0002] In recent years, three-dimensional carbon aerogel (3D-CAG) has attracted extensive attention in many fields such as energy storage, chemical catalysis and environmental protection due to its ultra-light weight, excellent pore structure, huge specific surface area and excellent conductivity, as well as its excellent performance in physical, chemical and mechanical stability. According to market analysis, the global market value of carbon aerogel is rising year by year at an astonishing rate, which provides a rare development opportunity for its low-cost and high-efficiency practical application.

[0003] At present, the preparation technology of three-dimensional carbon aerogel (3D-CAG) mainly covers the following methods:

[0004] (1) Sol-gel method: This is a widely used preparation process, which includes the preparation of sol, aging of gel, solvent exchange, drying and carbonization. However, this process not only has many steps, but also the gel aging stage is time-consuming, and the organic reagents used in the solvent exchange process (such as acetone) may also bring safety risks.

[0005] (2) Supercritical / pressure drying method: This method converts the filler into a supercritical fluid and fills it into the solid skeleton to maintain the integrity of the material structure when the filler is removed. However, its high preparation cost, complex operation process and long time make it difficult to achieve large-scale production.

[0006] (3) Pyrolysis method: It usually involves high-temperature pyrolysis of organic polymers or polymer systems under a protective atmosphere, thereby forming a large number of pores in the gel structure and constructing a carbon aerogel material with a three-dimensional porous structure. However, the shrinkage phenomenon that may occur during the pyrolysis process may affect the final performance of the product. In addition, the process of constructing the polymer system is complicated and the selectivity is limited, which also leads to an increase in cost.

[0007] (4) Hydrothermal method: This method is usually carried out in a reactor. Although it can obtain high-purity products, it faces the challenges of high temperature and high pressure, and the output is relatively low.

[0008] Other methods include chemical vapor deposition and ice template method, which can also prepare carbon aerogel materials. However, high cost and complicated process flow have become the main obstacles for these methods to be industrialized.

[0009] Regarding the above-mentioned related technologies, the inventors believe that traditional methods are generally complicated, time-consuming, costly, and dangerous, which is not conducive to commercial applications and greatly limits the potential of 3D-CAG in industrial-scale applications. Summary of the invention

[0010] In the related art, traditional methods are generally complicated, time-consuming, costly, and dangerous, which is not conducive to commercial application and greatly limits the potential of 3D-CAG in industrial-scale applications. In order to improve this defect, the present application provides a green and simple method for synthesizing three-dimensional carbon gel materials that can be used for electrochemical energy storage.

[0011] The present application provides a green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage, using the following technical solution:

[0012] A green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage comprises the following steps:

[0013] (1) preparing calcium carbonate nanoparticles using water-soluble calcium salt and water-soluble carbonate for later use;

[0014] (2) mixing an organic carbon source and calcium carbonate nanoparticles, adding water and a binder, and then aging for 12-24 hours to obtain an aged material; the binder is polyvinyl alcohol; the total weight of carbon in the organic carbon source is 0.78-1.41 times the total weight of calcium in the calcium carbonate nanoparticles in step (1);

[0015] (3) Under the protection of inert gas, the aged material is subjected to pyrolysis and carbonization treatment at a temperature of 550-820°C to obtain a carbon-calcium composite material;

[0016] (4) The carbon-calcium composite material is etched with protonic acid to obtain a three-dimensional carbon gel.

[0017] By adopting the above technical scheme, the present application first successfully prepared calcium carbonate nanoparticles. Then, the organic carbon source was mixed with the calcium carbonate nanoparticles, and water and a binder were added for aging treatment to form an aged material. Through further pyrolysis and carbonization treatment, the organic carbon source was converted into a carbon gel with a rich porous structure. Subsequently, the calcium carbonate nanoparticles were removed by precise etching of protonic acid, and finally a pure three-dimensional carbon gel was obtained. Compared with the traditional preparation method, the method of the present application is simpler in process, less time-consuming and lower in cost. During the entire preparation process, there is almost no need to use highly volatile organic solvents, thereby greatly reducing the emission of volatile organic compounds (VOCs). In addition, the organic carbon source has a wide range of materials, which can be waste such as agricultural straw and domestic garbage, which not only promotes the resource recycling of waste, but also reflects the green and environmentally friendly characteristics of the present method. In summary, the three-dimensional carbon gel preparation method of the present application has opened up a new path for the sustainable development of carbon aerogel materials with its multiple advantages such as high efficiency, environmental protection and economy, fully overcomes the defects in related technologies, and is suitable for commercial use.

[0018] Preferably, in step (2), an activator is mixed with an organic carbon source and calcium carbonate nanoparticles, and then water and a binder are added, wherein the activator comprises a metal chloride salt, and the metal chloride salt is one of ferric chloride, aluminum chloride and zinc chloride.

[0019] By adopting the above technical solution, the present application preferably selects the activator to include a metal chloride salt, and preferably the specific type of the metal chloride salt. The metal chloride salt can enable the organic carbon source to form a relatively developed and rich pore structure during the carbonization process, which helps to increase the specific surface area of ​​the three-dimensional carbon gel.

[0020] Preferably, the amount of the activator is 3-5% of the total weight of the organic carbon source.

[0021] By adopting the above technical solution, the present application optimizes the dosage of the activator, which helps to fully activate the organic carbon source.

[0022] Preferably, the organic carbon source comprises at least one of glucose, citric acid, starch, sawdust, straw, wood chips and corn cobs.

[0023] By adopting the above technical scheme, the present application adopts at least one of glucose, citric acid, starch, sawdust, straw, wood chips, and corn cobs as an organic carbon source, and prepares a three-dimensional carbon gel, each of which has unique advantages and beneficial effects. Glucose, due to its high reactivity and easy conversion to carbon, helps to form a uniform carbon structure; the active sites formed by the carboxyl groups of citric acid during the pyrolysis process increase the porosity and specific surface area of ​​the carbon gel; starch, as a polysaccharide, provides a stable carbon skeleton and produces a rich pore structure. At the same time, sawdust, straw, wood chips and corn cobs, which are by-products of agriculture and wood processing, are not only low-cost and promote the resource utilization of waste, but also because of the cellulose and lignin components they contain, a carbon material with good chemical stability and porosity is formed during the pyrolysis process. The comprehensive use of these organic carbon sources not only reduces the preparation cost and enhances the environmental friendliness of the material, but also provides great flexibility for adjusting the pore structure and chemical composition of the carbon gel, thereby optimizing the performance of the material and meeting the needs of different application scenarios.

[0024] Preferably, the organic carbon source also includes phytic acid.

[0025] By adopting the above technical solution, phytic acid is a phosphorus-containing organic acid with a wide range of sources in nature and the advantages of being non-toxic and non-polluting. In addition to participating in the formation of carbonized products as an organic carbon source, phytic acid can also combine with metal ions during the aging process, improving the combination effect of metal ions and organic carbon sources, allowing the activator to more fully exert its activation effect. In addition, it can also decompose and produce phosphoric acid during carbonization, which promotes the formation of carbonized products and helps to improve the product performance of three-dimensional carbon gel.

[0026] Preferably, the organic carbon source also includes polyacrylonitrile regeneration material, and the polyacrylonitrile regeneration material is prepared according to the following method: crushing discarded acrylic fiber to obtain fiber powder, using a mixed solvent of DMSO and water to disperse the fiber powder, and obtaining a polyacrylonitrile solution after stirring and dissolving; allowing the polyacrylonitrile solution to stand until phase separation occurs, taking out the phase separation product from the liquid phase, extracting the phase separation product with ethanol, and then freeze-drying the phase separation product, and crushing the dry product to obtain the polyacrylonitrile regeneration material.

[0027] By adopting the above technical scheme, the present application uses waste acrylic fiber as raw material, dissolves the waste acrylic fiber by DMSO, and regenerates the polyacrylonitrile dissolved in DMSO by standing separation, extraction and freeze drying, and obtains polyacrylonitrile regeneration material. The polyacrylonitrile regeneration material of the present application can form a pore structure during the freeze drying process, and on this basis, polyacrylonitrile can also produce a certain amount of gas during the carbonization process. Under the pore-forming effect of the gas and the combined effect of phytic acid and metal chloride salts, the three-dimensional carbon gel of the present application can have a more complex pore structure and better product performance.

[0028] Preferably, the calcium carbonate nanoparticles are prepared according to the following method:

[0029] (1) using a water-soluble carbonate to prepare a carbonate solution for later use; using a water-soluble calcium salt to prepare a calcium salt solution for later use; the molar ratio of carbonate ions in the water-soluble carbonate to calcium ions in the water-soluble calcium salt is 1:1;

[0030] (2) Adding the carbonate solution into the calcium salt solution, stirring the solution for reaction, and then standing, washing, filtering and drying the solution to obtain calcium carbonate nanoparticles.

[0031] By adopting the above technical solution, the present application preferably provides a method for preparing calcium carbonate nanoparticles. According to the above method, calcium carbonate nanoparticles with a particle size that meets the requirements can be obtained, and the preparation of three-dimensional carbon gel can be achieved.

[0032] Preferably, in the step (2) of preparing the calcium carbonate nanoparticles, sodium polystyrene sulfonate and carbonate solution are added to the calcium salt solution.

[0033] By adopting the above technical solution, sodium polystyrene sulfonate is a surfactant. The addition of this surfactant can make the calcium carbonate nanoparticles have a porous morphology. Since the shape of the carbon gel is complementary to the calcium carbonate nanoparticles to a certain extent, this method helps to increase the specific surface area of ​​the three-dimensional carbon gel.

[0034] Preferably, the weight average molecular weight of the sodium polystyrene sulfonate is 65-75 kDa.

[0035] By adopting the above technical solution, the present application optimizes the weight average molecular weight of sodium polystyrene sulfonate. Within this range, the calcium carbonate nanoparticles can have a porous morphology, which helps to increase the specific surface area of ​​the three-dimensional carbon gel.

[0036] Preferably, the weight ratio between the sodium polystyrene sulfonate and the carbonate ions in the water-soluble carbonate is 1:(2.8-3.2).

[0037] By adopting the above technical solution, the present application optimizes the dosage range of sodium polystyrene sulfonate, within which the calcium carbonate nanoparticles can have a porous morphology, which helps to increase the specific surface area of ​​the three-dimensional carbon gel.

[0038] In summary, this application has the following beneficial effects:

[0039] 1. The present invention uses low-cost, green and non-toxic calcium carbonate as a template, and the synthesis and removal methods are simple, effective and safe, which is convenient for large-scale production and commercial application.

[0040] 2. Compared with the traditional method, the present invention has low cost, is green and environmentally friendly, and the raw materials can be recovered and recycled (such as water-soluble carbonates and water-soluble calcium salts).

[0041] 3. The porous carbon gel obtained in this application has rich porosity. In addition to macropores, at a certain temperature, carbon dioxide produced by the decomposition of calcium carbonate will also be produced, making the system rich in micropores, with a stable structure and adjustable pore size, which can meet the requirements of different application conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a SEM image of the three-dimensional carbon gel of Example 1 of the present application.

[0043] Figure 2 This is the specific surface area curve of the three-dimensional carbon gel in Example 1 of the present application.

[0044] Figure 3 This is the porosity curve of the three-dimensional carbon gel of Example 1 of the present application.

[0045] Figure 4 This is the XRD pattern of the three-dimensional carbon gel of Example 1 of the present application. DETAILED DESCRIPTION

[0046] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0047] Preparation example of calcium carbonate nanoparticles

[0048] The following is an explanation using Preparation Example 1.

[0049] Preparation Example 1

[0050] In this preparation example, calcium carbonate nanoparticles were prepared according to the following method:

[0051] (1) Using sodium carbonate to prepare a 0.025 mol / L carbonate solution, magnetically stirring at a rate of 500 r / min for 45 min in a water bath at 80°C, and setting aside; using calcium chloride to prepare a 0.025 mol / L calcium salt solution at 45°C, magnetically stirring at a rate of 500 r / min for 45 min, and setting aside; the molar ratio of carbonate ions in the water-soluble carbonate to calcium ions in the water-soluble calcium salt is 1:1;

[0052] (2) Adding the carbonate solution to the calcium salt solution within 10 seconds, ultrasonically treating at a power of 900 W for 10 seconds, stirring the reaction and standing for 24 hours, then washing, filtering and drying to obtain calcium carbonate nanoparticles.

[0053] Preparation Example 2

[0054] The difference between this preparation example and preparation example 1 is that in step (2) of preparing calcium carbonate nanoparticles, sodium polystyrene sulfonate and carbonate solution are added together to the calcium salt solution, the weight average molecular weight of sodium polystyrene sulfonate is 65 kDa, and the weight ratio between sodium polystyrene sulfonate and carbonate ions in water-soluble carbonate is 1:2.8.

[0055] Preparation Example 3

[0056] The difference between this preparation example and preparation example 1 is that in step (2) of preparing calcium carbonate nanoparticles, sodium polystyrene sulfonate and carbonate solution are added together to the calcium salt solution, the weight average molecular weight of sodium polystyrene sulfonate is 70 kDa, and the weight ratio between sodium polystyrene sulfonate and carbonate ions in water-soluble carbonate is 1:3.0.

[0057] Preparation Example 4

[0058] The difference between this preparation example and preparation example 1 is that in step (2) of preparing calcium carbonate nanoparticles, sodium polystyrene sulfonate and carbonate solution are added together to the calcium salt solution, the weight average molecular weight of sodium polystyrene sulfonate is 75 kDa, and the weight ratio between sodium polystyrene sulfonate and carbonate ions in water-soluble carbonate is 1:3.2.

[0059] Preparation example of polyacrylonitrile recycled material

[0060] The following is an explanation using Preparation Example 5.

[0061] Preparation Example 5

[0062] In this preparation example, polyacrylonitrile recycled material is prepared according to the following method:

[0063] Waste acrylic fiber (100% acrylic, 28s) was crushed to obtain fiber powder, and the fiber powder was dispersed with a mixed solvent of DMSO and water (DMSO mass fraction 88%). After stirring and dissolving for 5 hours at 80°C and 380rpm, a polyacrylonitrile solution was obtained. The polyacrylonitrile solution was allowed to stand at 20°C until phase separation occurred, and the phase separation product was taken out from the liquid phase. The phase separation product was extracted with ethanol for three consecutive extractions, each extraction time being 12 hours. After the extraction, the phase separation product was vacuum freeze-dried, and the dried product was crushed to obtain a polyacrylonitrile recycled material with an average particle size of 0.1 mm.

[0064] Example

[0065] Examples 1-4

[0066] The following description is given by taking Example 1 as an example.

[0067] Example 1

[0068] This embodiment provides a green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage, comprising the following steps:

[0069] (1) According to the method of Preparation Example 1, calcium carbonate nanoparticles are prepared using water-soluble calcium salt and water-soluble carbonate, and the prepared particles are set aside;

[0070] (2) An organic carbon source and calcium carbonate nanoparticles are mixed in a weight ratio of 1:1.3, and after adding water and a binder, an aging treatment is performed for 12 hours to obtain an aged material; the binder is polyvinyl alcohol; the binder is polyvinyl alcohol 17-99, the amount of the binder is 1% of the total weight of the organic carbon source, and the amount of water is 15% of the total weight of the organic carbon source; the organic carbon source is prepared by mixing glucose, red pine sawdust, corn stalks, and corn cobs in a weight ratio of 8:1:1; the total weight of carbon in the organic carbon source is 0.78 times the total weight of calcium in the calcium carbonate nanoparticles of step (1);

[0071] (3) Under the protection of inert gas, the aged material was subjected to pyrolysis carbonization treatment at a temperature of 550°C for 3 hours to obtain a carbon-calcium composite material;

[0072] (4) The carbon calcium composite material is etched with proton acid to obtain a three-dimensional carbon gel; the proton acid is hydrochloric acid with a pH value of 2.6, and the etching time is 24 hours.

[0073] Example 2

[0074] This embodiment provides a green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage, comprising the following steps:

[0075] (1) According to the method of Preparation Example 2, calcium carbonate nanoparticles are prepared using water-soluble calcium salt and water-soluble carbonate, and the prepared particles are set aside;

[0076] (2) An organic carbon source, calcium carbonate nanoparticles and an activator are mixed in a weight ratio of 1:1.3:0.03, and after adding water and a binder, an aging treatment is performed for 18 hours to obtain an aged material; the activator is aluminum chloride, and the binder is polyvinyl alcohol; the binder is polyvinyl alcohol 17-99, the amount of the binder is 1% of the total weight of the organic carbon source, and the amount of water is 15% of the total weight of the organic carbon source; the organic carbon source is prepared by mixing glucose, citric acid, corn starch and birch sawdust in a weight ratio of 5:3:1:1; the total weight of carbon in the organic carbon source is 0.94 times the total weight of calcium in the calcium carbonate nanoparticles of step (1);

[0077] (3) Under the protection of inert gas, the aged material was subjected to pyrolysis carbonization treatment at a temperature of 680°C for 3 hours to obtain a carbon-calcium composite material;

[0078] (4) The carbon calcium composite material is etched with proton acid to obtain a three-dimensional carbon gel; the proton acid is hydrochloric acid with a pH value of 2.6, and the etching time is 24 hours.

[0079] Example 3

[0080] This embodiment provides a green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage, comprising the following steps:

[0081] (1) According to the method of Preparation Example 3, calcium carbonate nanoparticles are prepared using water-soluble calcium salt and water-soluble carbonate, and the prepared particles are set aside;

[0082] (2) An organic carbon source, calcium carbonate nanoparticles and an activator are mixed in a weight ratio of 1:1.3:0.04, and after adding water and a binder, an aging treatment is performed for 22 hours to obtain an aged material; the activator is zinc chloride, and the binder is polyvinyl alcohol; the binder is polyvinyl alcohol 17-99, the amount of the binder is 1% of the total weight of the organic carbon source, and the amount of water is 15% of the total weight of the organic carbon source; the organic carbon source is prepared by mixing glucose, citric acid, corn starch and birch sawdust in a weight ratio of 5:3:1:1; the total weight of carbon in the organic carbon source is 1.22 times the total weight of calcium in the calcium carbonate nanoparticles of step (1);

[0083] (3) Under the protection of inert gas, the aged material is subjected to pyrolysis and carbonization treatment at a temperature of 760°C to obtain a carbon-calcium composite material;

[0084] (4) The carbon calcium composite material is etched with proton acid to obtain a three-dimensional carbon gel; the proton acid is hydrochloric acid with a pH value of 2.6, and the etching time is 24 hours.

[0085] Example 4

[0086] This embodiment provides a green and simple method for synthesizing a three-dimensional carbon gel material that can be used for electrochemical energy storage, comprising the following steps:

[0087] (1) According to the method of Preparation Example 4, calcium carbonate nanoparticles are prepared using water-soluble calcium salt and water-soluble carbonate, and the prepared particles are set aside;

[0088] (2) An organic carbon source, calcium carbonate nanoparticles and an activator are mixed in a weight ratio of 1:1.3:0.05, and after adding water and a binder, an aging treatment is performed for 24 hours to obtain an aged material; the activator is ferric chloride, and the binder is polyvinyl alcohol; the binder is polyvinyl alcohol 17-99, the amount of the binder is 1% of the total weight of the organic carbon source, and the amount of water is 15% of the total weight of the organic carbon source; the organic carbon source is prepared by mixing glucose, citric acid, corn starch and birch sawdust in a weight ratio of 5:3:1:1; the total weight of carbon in the organic carbon source is 1.41 times the total weight of calcium in the calcium carbonate nanoparticles of step (1);

[0089] (3) Under the protection of inert gas, the aged material is subjected to pyrolysis and carbonization treatment at a temperature of 820° C. to obtain a carbon-calcium composite material;

[0090] (4) The carbon calcium composite material is etched with proton acid to obtain a three-dimensional carbon gel; the proton acid is hydrochloric acid with a pH value of 2.6, and the etching time is 24 hours.

[0091] Example 5

[0092] The difference between this embodiment and embodiment 4 is that the organic carbon source is prepared by mixing glucose, citric acid, corn starch, birch sawdust and phytic acid in a weight ratio of 4:3:1:1:1.

[0093] Example 6

[0094] The difference between this embodiment and embodiment 5 is that the organic carbon source is prepared by mixing glucose, citric acid, corn starch, birch sawdust, phytic acid and the polyacrylonitrile recycled material of preparation example 5 in a weight ratio of 4:3:1:1:1:2.

[0095] Comparative Example

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that the pyrolysis temperature of the aged material is 480°C.

[0098] Comparative Example 2

[0099] The difference between this comparative example and Example 1 is that the pyrolysis temperature of the aged material is 850°C.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that the total weight of carbon elements in the organic carbon source is 0.62 times the total weight of calcium elements in the calcium carbonate nanoparticles in step (1).

[0102] Comparative Example 4

[0103] The difference between this comparative example and Example 1 is that the total weight of carbon elements in the organic carbon source is 1.55 times the total weight of calcium elements in the calcium carbonate nanoparticles in step (1).

[0104] Performance testing methods

[0105] 1. SEM image

[0106] The three-dimensional carbon gel of Example 1 was observed using SEM, and the results are shown in Figure 1 .

[0107] 2. Specific surface area

[0108] The specific surface area of ​​carbon aerogel was detected according to the method described in GB / T 19587-2017 Determination of specific surface area of ​​solid matter by gas adsorption BET method, and the specific surface area of ​​Example 1 was used as a benchmark to calculate the ratio between the specific surface area of ​​each example and comparative example and the specific surface area of ​​Example 1, and the ratio was recorded as the relative specific surface area. The results are shown in Table 1. In addition, the specific surface area curve of Example 1 is shown in Figure 2 .

[0109] 3. Porosity curve

[0110] The porosity of the three-dimensional carbon gel of Example 1 was tested, and the results are shown in Figure 3 .

[0111] 4. XRD pattern

[0112] The three-dimensional carbon gel of Example 1 was subjected to XRD detection, and the results are shown in Figure 4 .

[0113] 5. Cycle performance

[0114] Three-dimensional carbon gel, acetylene black and sodium hydroxymethyl cellulose were mixed in a weight ratio of 8:1:1, and then deionized water was added and stirred to form a slurry. 2 The slurry was coated on copper foil in an amount of 200 μg / cm2 and then punched to obtain an electrode. The obtained electrode was assembled into a CR2032 button battery. The electrolyte was LiPF 6Dissolved in a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DEC) at a concentration of 1 mol / L (the volume ratio of EC to DEC is 1:1), and 6 wt% FEC was added as an additive. The cycle performance was tested using a charge and discharge tester (CT3001A). The battery was first activated for 3 cycles at a low current of 100 mA / g, and then cycled for 200 cycles at a high current of 200 mA / g. The specific capacity after 200 cycles was tested, and the results are shown in Table 2.

[0115] Table 1 Relative specific surface area

[0116]

[0117] Table 2 Specific capacity

[0118]

[0119] Combination Figure 1 It can be seen that the three-dimensional carbon gel of Example 1 has fully formed a pore structure.

[0120] Combination Figure 2 It can be seen that the three-dimensional carbon gel of Example 1 has a larger specific surface area.

[0121] Combination Figure 3 It can be seen that the three-dimensional carbon gel of Example 1 has a large number of micro-nano pores.

[0122] Combination Figure 4 It can be seen that for the three-dimensional carbon gel of Example 1, an obvious bulging peak is located between 20 and 30°, indicating the presence of amorphous carbon.

[0123] Combining Examples 1-4 and Comparative Examples 1-4 and Table 1, it can be seen that within the process parameter range specified in the present application, the three-dimensional carbon gel has a large specific surface area, and with the addition of an activator and sodium polystyrene sulfonate, the specific surface area of ​​the three-dimensional carbon gel can be further increased. Compared with the traditional preparation method, the method of the present application is simpler in process, less time-consuming and lower in cost. During the entire preparation process, almost no organic solvent is required, thereby greatly reducing the emission of volatile organic compounds (VOCs). The organic carbon source of the present application has a wide range of material selection, which can be waste such as agricultural straw and domestic garbage, which not only promotes the resource recycling of waste, but also reflects the green and environmentally friendly characteristics of the present method. Therefore, the three-dimensional carbon gel preparation method provided in the present application has opened up a new path for the sustainable development of carbon aerogel materials with its multiple advantages such as high efficiency, environmental protection, and economy, fully overcomes the defects in the relevant technology, and is suitable for commercial use.

[0124] It can be seen from Examples 1-6 and Comparative Examples 1-4 and Table 2 that the specific capacity of the batteries prepared using the three-dimensional carbon gel of Examples 1-6 after 200 cycles is above 570 mAh / g, indicating that the three-dimensional carbon gel prepared in the present application has long cyclability, high capacity and excellent structural stability.

[0125] It can be seen from Example 4 and Example 5 and Table 1 that after adding phytic acid to the organic carbon source, the specific surface area of ​​the three-dimensional carbon gel is further expanded. This is because in addition to participating in the formation of carbonized products as an organic carbon source, phytic acid can also combine with metal ions during the aging process, improving the combination effect of metal ions and organic carbon sources, so that the activator can more fully exert its activation effect. In addition, it can also decompose and produce phosphoric acid during carbonization, which promotes the formation of carbonized products and helps to improve the product performance of the three-dimensional carbon gel.

[0126] It can be seen from Example 5 and Example 6 and Table 1 that after further adding polyacrylonitrile regenerated material to the organic carbon source, the specific surface area of ​​the three-dimensional carbon gel is further increased, indicating that under the pore-forming effect of the gas and the combined effect of phytic acid and metal chloride salts, the three-dimensional carbon gel of the present application can have a more complex pore structure and better product performance.

[0127] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application as needed without any creative contribution. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A green and simple method for synthesizing three-dimensional carbon gel materials for electrochemical energy storage, characterized in that: The following steps are involved: (1) preparing calcium carbonate nanoparticles using water-soluble calcium salt and water-soluble carbonate for later use; (2) mixing an organic carbon source and calcium carbonate nanoparticles, adding water and a binder, and then aging for 12-24 hours to obtain an aged material; the binder is polyvinyl alcohol; the total weight of carbon in the organic carbon source is 0.78-1.41 times the total weight of calcium in the calcium carbonate nanoparticles in step (1); (3) Under the protection of inert gas, the aged material is subjected to pyrolysis and carbonization treatment at a temperature of 550-820°C to obtain a carbon-calcium composite material; (4) Etching the carbon-calcium composite material with proton acid to obtain a three-dimensional carbon gel; Wherein, in step (2), an activator is mixed with an organic carbon source and calcium carbonate nanoparticles, and then water and a binder are added, wherein the activator comprises a metal chloride salt, and the metal chloride salt is one of ferric chloride, aluminum chloride, and zinc chloride; The organic carbon source includes at least one of glucose, citric acid, starch, straw, sawdust, and corn cobs; The organic carbon source also includes phytic acid; The organic carbon source also includes polyacrylonitrile regeneration material, and the polyacrylonitrile regeneration material is prepared according to the following method: crushing discarded acrylic fiber to obtain fiber powder, using a mixed solvent of DMSO and water to disperse the fiber powder, and obtaining a polyacrylonitrile solution after stirring and dissolving; allowing the polyacrylonitrile solution to stand until phase separation occurs, taking out the phase separation product from the liquid phase, extracting the phase separation product with ethanol, and then freeze-drying the phase separation product, and crushing the dry product to obtain the polyacrylonitrile regeneration material.

2. The green and simple method for preparing three-dimensional carbon gel according to claim 1, characterized in that: The amount of the activator used is 3-5% of the total weight of the organic carbon source.

3. The green and simple method for preparing three-dimensional carbon gel according to claim 1, characterized in that: The calcium carbonate nanoparticles are prepared according to the following method: (1) using a water-soluble carbonate to prepare a carbonate solution for later use; using a water-soluble calcium salt to prepare a calcium salt solution for later use; the molar ratio of carbonate ions in the water-soluble carbonate to calcium ions in the water-soluble calcium salt is 1:1; (2) Adding the carbonate solution into the calcium salt solution, stirring the solution for reaction, and then standing, washing, filtering and drying the solution to obtain calcium carbonate nanoparticles.

4. The green and simple method for preparing three-dimensional carbon gel according to claim 3, characterized in that: In the step (2) of preparing the calcium carbonate nanoparticles, sodium polystyrene sulfonate and carbonate solution are added into the calcium salt solution.

5. The green and simple method for preparing three-dimensional carbon gel according to claim 4, characterized in that: The weight average molecular weight of the sodium polystyrene sulfonate is 65-75 kDa.

6. The green and simple method for preparing three-dimensional carbon gel according to claim 4, characterized in that: The weight ratio between the sodium polystyrene sulfonate and the carbonate ions in the water-soluble carbonate is 1:(2.8-3.2).